Coach 2023 / Ili Rabiatul Adawiah Ismail, Muhammad ‘Izzuddin Zamery and Assoc. Prof. Dr. Mahmathi Karuppannan - Ismail, Ili Rabiatul Adawiah; Zamery, Muhammad ‘Izzuddin; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
In early April, the Sekretariat Mahasiswa Fakulti Farmasi (SMF) and Society of Pharmacy Students (SOPHYS) organized a program called COACH 2023. The event was held on the 1st of April, 2023, at Dewan Kuliah 500. COACH 2023 was designed to introduce the committee members on the process of organising events in the campus and to enhance their leadership skills. The program was a full-day event, running from 10 AM to 8 PM. The day was filled with exciting activities, including mini-games, a briefing on organization management and development by Dr. Aida Azlina, COACH module briefing, and hands-on sessions